Interactions Between Citrus Viroids Affect Symptom Expression and Field Performance of Clementine Trees Grafted on Trifoliate Orange - Verniere, C.; Perrier, Xavier; Dubois, C.; Dubois, A.; Botella, L.; Chabrier, C.; Bove, J. M.; Durán-Vila, Núria (The American Phytopathological Society (APS), 2022)
Citrus exocortis viroid (CEVd), Citrus bent leaf viroid (CBLVd), a noncachexia variant of Hop stunt viroid (HSVd), Citrus viroid III (CVd-III), and Citrus viroid IV (CVd-IV) were co-inoculated as two-, three-, four-, and five-viroid mixtures to Clementine trees grafted on trifoliate orange to evaluate their effect on symptom expression, tree growth, and fruit yield. Most trees infected with CEVd-containing viroid mixtures developed exocortis scaling symptoms, as did CEVd alone, whereas most trees infected with HSVd- or CVd-IV-containing mixtures developed bark-cracking symptoms. Trees infected with mixtures containing both CEVd and CVd-IV revealed the existence of antagonism between these two viroids in terms of the expected bark-scaling and cracking symptoms. Synergistic interactions also were identified in trees infected with certain viroid combinations that, in spite of lacking CEVd, expressed exocortis-like scaling symptoms. Viroid interactions also affected the expected response of trees in terms of vegetative growth and fruit yield. Trees infected with viroid combinations containing CEVd or CVd-III were smaller and produced less fruit than trees infected with mixtures not containing these viroids. Viroid interactions on scion circumference and cumulative fruit yield, in terms of additivity of their effects, were statistically confirmed using a factorial analysis of variance model with two mean estimation approaches. In single-viroid infections, CEVd, CVd-III, and, to a lesser extent, CBLVd consistently and significantly reduced tree size and fruit yield. Conversely, HSVd and CVd-IV slightly increased fruit yield and reduced scion circumference. Rare and not consistent significant interactions were detected with the five-, four-, and three-viroid combinations. Antagonistic interactions between CEVd and CVd-III or CBLVd and CVd-III were revealed over the years with consistent significance. The antagonistic interaction between CEVd and CVd-IV was highly significant over the years when additional viroids were present; however, this antagonism appeared much later in the case of an exclusive interaction. HSVd and CVd-IV showed a consistent and significant synergistic interaction on yield only when both viroids were exclusively present. These results demonstrate antagonistic or synergistic relationships between citrus viroids depending on the viroid mixtures present in the host.